2014
DOI: 10.3389/fphys.2014.00188
|View full text |Cite
|
Sign up to set email alerts
|

The buffer capacity of airway epithelial secretions

Abstract: The pH of airway epithelial secretions influences bacterial killing and mucus properties and is reduced by acidic pollutants, gastric reflux, and respiratory diseases such as cystic fibrosis (CF). The effect of acute acid loads depends on buffer capacity, however the buffering of airway secretions has not been well characterized. In this work we develop a method for titrating micro-scale (30 μl) volumes and use it to study fluid secreted by the human airway epithelial cell line Calu-3, a widely used model for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 46 publications
6
27
0
Order By: Relevance
“…The slow change in pH ASL was a result of low carbonic anhydrase activity of the ASL. These data are consistent with previous reports that ASL removed from epithelia has minimal carbonic anhydrase activity (Candiano et al 2007;Kim et al 2014). Thus, loss of carbonic anhydrase activity in the bulk ASL may represent an evolutionary selection to minimize dynamic changes in pH ASL in response to respiration.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The slow change in pH ASL was a result of low carbonic anhydrase activity of the ASL. These data are consistent with previous reports that ASL removed from epithelia has minimal carbonic anhydrase activity (Candiano et al 2007;Kim et al 2014). Thus, loss of carbonic anhydrase activity in the bulk ASL may represent an evolutionary selection to minimize dynamic changes in pH ASL in response to respiration.…”
Section: Discussionsupporting
confidence: 92%
“…The reaction CO 2 + H 2 O ↔ H + + HCO 3 – is catalyzed by carbonic anhydrase (Kim et al. ). Because the observed pH change is slow, we predicted that carbonic anhydrase activity is low within intact ASL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Normal airway surface liquid (ASL) has a pH of around 7.0 (estimated bicarbonate concentration of approximately 10–20 mMol). A recent review describes the evidence that ASL pH is controlled by bicarbonate secretion via CFTR and other secreted proteins . CFTR in airway cells derived from a lung cancer cell line (Calu‐3) will secrete either bicarbonate or chloride, depending on the activity of basolateral membrane cotransporters .…”
Section: Ionic Content and Fluid On Epithelial Surfacesmentioning
confidence: 99%
“…The * indicates the difference from epithelia with 100% WT cells by repeated measures ANOVA, P < 0.05. epithelium are WT or overexpress CFTR, Cl − secretion rises to the level of WT epithelia (10)(11)(12)(13)(14). However, knowledge that CFTR conducts HCO 3 − (48), that HCO 3 − is the major pH buffer of ASL (49), and that HCO 3 − secretion plays a key role in airway host defense (31)(32)(33)(34)(35)50) led us to test the relationship between CFTR expression and HCO 3 − secretion. We found that, unlike Cl − secretion, HCO 3 − secretion was directly proportional to CFTR expression.…”
Section: Increasing Cftr Expression Progressively Enhances Asl Host Dmentioning
confidence: 99%